Methodology For the Development of Creative Competencies of Future Educators on the Basis of Forsyth Technologies - Mouminov Komiljon Akhmadzhonov (Periodica Journal, 2023)
This article is intended for students of the pedagogical academy studying in the direction of undergraduate education and teachers of the pedagogical higher education professor. In the methodological improvement of students ' creative competencies on the basis of Forsyth technologies, pedagogical conditions and quality indicators of the application of innovative organizational and didactic forms of education, information and didactic provision are described. The methodology for improving students ' creative competencies on the basis of Forsyth Technologies, is highlighted on the basis of an innovative approach
Keywords: Technologies; highlighted; innovative; conditions